2020
DOI: 10.21203/rs.3.rs-18029/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Level of Vaccination and Protection Against Hepatitis B with Low Rate of Hepatitis C HCV infection Markers among Hospital Health Care Personnel in North of Iran: A cross-Sectional study.

Abstract: Background: hepatitis B virus (HBV) and C virus (HCV) are among the leading causes of mortality worldwide. Health care personnel (HCP) are subjected to increased risk of these infections. Therefore, HBV vaccination and post-vaccination serologic testing (PVST) are recommended for them. Our Objectives in this study were investigate how well the vaccination guidelines for hospital HCPs were implemented. Moreover, the prevalence rates of HBV and HCV infections were calculated. To determine the presence of immunol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In a similar study reported by Dowran et al (17), from Shiraz, Iran; none of the studied HSS was HBsAg positive, but 1.1% were anti-HBc positive. As was reported in the world (1,2,5,7), well planned vaccination strategy implemented during the last 3 decades in the Iran, largely contributed to the control of HBV infection both in the community and in the several occupational settings, especially among healthcare personnel's/trainees (18)(19)(20).…”
Section: Hepatitis B Immunity Status Among Healthcare Sciences Studen...mentioning
confidence: 87%
“…In a similar study reported by Dowran et al (17), from Shiraz, Iran; none of the studied HSS was HBsAg positive, but 1.1% were anti-HBc positive. As was reported in the world (1,2,5,7), well planned vaccination strategy implemented during the last 3 decades in the Iran, largely contributed to the control of HBV infection both in the community and in the several occupational settings, especially among healthcare personnel's/trainees (18)(19)(20).…”
Section: Hepatitis B Immunity Status Among Healthcare Sciences Studen...mentioning
confidence: 87%